Effectiveness of Virgin Coconut Oil (VCO) on Changes in Weight and Height among Under-five Children with Stunting - Retno Setyo Iswati; Indria Nuraini (EMBRIO: Jurnal Kebidanan, 2023)
Virgin Coconut Oil (VCO) is a type of vegetable oil that can facilitate the food digestion and nutrients absorption processes. VCO contains plus minus 10percent unsaturated fatty acids and plus minus 90percent saturated fatty acids. Besides fat, VCO also contains micronutrients. Administering VCO to under-five children with stunting aims to improve metabolic function so as to increase immunity, optimize growth and development and quality of child health status. This study aims to determine the effectiveness of Virgin Coconut Oil (VCO) on changes in body weight and height among under-five children with stunting. This was a Quasi-Experimental study with a Non Equivalent Control Group design. The samples involved 32 under-five children with stunting. The intervention by administering VCO at a dose of 1 X 5 ml before eating in the morning was conducted for 30 days. Data were analyzed using paired t-test. The results of the study found that administration of VCO was not proven to be effective in significantly increasing body weight (p equals 0.693) and height (p equals 0.548) among under-five children with stunting (p more than 0.05).